Merab Mamardashvili: Event of Thought and Pedagogic Practice - D. G. Ryndin (Высшее образование в России)
The concept of event has been widely disseminated in various fields of human sciences, including the psychology of education and pedagogics. If one seeks to explore the full heuristic potential of the concept, it is necessary to take into account its essential affiliation with non-classical ontology. The article presents an attempt to analyze the inner structure of Merab Mamardashvili’s oral philosophical speech, that can be considered a distinctive feature of the series of lection courses, which he held in the late 70-ies – beginning of 80-ies mainly for the audience of non-philosophers. The article deals with the research of essential connection between form and content of Mamardashvili’s philosophy. In the light of this connection the article reviews the project of the non-classical ontology of cognition, that Mamardashvili develops in some of his main works.The first part of the article contains an exposition of the problem field of “event” in the context of history and ontology of cognition, as well as reconstruction of the genesis of this theme in Mamardashvili’s philosophy. Mamardashvili describes the classical type of rationality and its “blind spots” – that is, historicity and “evental” character of phenomena of cognition, which cannot be seen in the objectifying gaze of the classical observer. An attempt is made to analyze Mamardashvili’s concept of conscience in the context of his phenomenology of event. The term “epiphany” is interpreted as a key characteristic of events of cognition.The second part of the article deals with the uniqueness of Merab Mamardashvili’s oral philosophical speech, that is interpreted as one of the strategies of indirect communication. Indirect communication is distinguished from direct communication of knowledge, the central model of classical pedagogics. The article studies several different approaches to interpretation of Merab Mamardashvili’s teaching strategy and proposes the approach that is based on the concept of indirect communication of event of cognition.